2015
DOI: 10.1074/jbc.m114.610493
|View full text |Cite
|
Sign up to set email alerts
|

Organelle-specific Subunit Interactions of the Vertebrate Two-pore Channel Family

Abstract: Background:The role of two-pore channels (TPCs) in endolysosomal signaling remains controversial. Results: TPCs are targeted to different subpopulations of endolysosomes, and this determines subunit interaction and Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…In contrast, however, another study in which a slightly different variant of urchin TPC3 was expressed in a different cell line did not observe such inhibitory properties for this TPC3, the expression of which was instead shown to enhance NAADP-induced Ca 2+ release, similar to the urchin TPC1 and TPC2 also assessed in this study (Brailoiu et al, 2010). Interestingly, a recent study of rabbit and chicken TPC3 isoforms has found no evidence that either of these vertebrate TPC3 isoforms can act in a dominant negative manner, although expression of chicken TPC3 did not lead to enhanced NAADP-induced Ca 2+ release, unlike expression of rabbit TPC3, which did (Ogunbayo et al, 2015).…”
Section: Role Of Naadp and Tpcs During Fertilization And Embryogenesismentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast, however, another study in which a slightly different variant of urchin TPC3 was expressed in a different cell line did not observe such inhibitory properties for this TPC3, the expression of which was instead shown to enhance NAADP-induced Ca 2+ release, similar to the urchin TPC1 and TPC2 also assessed in this study (Brailoiu et al, 2010). Interestingly, a recent study of rabbit and chicken TPC3 isoforms has found no evidence that either of these vertebrate TPC3 isoforms can act in a dominant negative manner, although expression of chicken TPC3 did not lead to enhanced NAADP-induced Ca 2+ release, unlike expression of rabbit TPC3, which did (Ogunbayo et al, 2015).…”
Section: Role Of Naadp and Tpcs During Fertilization And Embryogenesismentioning
confidence: 59%
“…2). Humans and mice have two functional TPC isoforms, TPC1 and TPC2; a third isoform, TPC3, present in many vertebrates including rabbits and chickens (Ogunbayo et al, 2015), is the product of a pseudogene that does not encode a functional protein in humans, Old World monkeys, apes, mice or rats (Calcraft et al, 2009, Cai and. Cai and Patel (2010) have characterised the evolutionary process that led to the degeneration of the TPC3 gene and loss of its protein's function in the primate lineage.…”
Section: Two-pore Channels As Naadp-regulated Ca 2+ Channelsmentioning
confidence: 99%
“…On plasma membranes, fish and frog TPC3 behave as voltage-gated, Na + -selective channels, insensitive to PI(3,5)P 2 and PI(4,5)P 2 [44]. On endolysosomes, chicken and rat TPC3 may conduct Ca 2+ ions in response to NAADP [36], whereas conflicting reports of invertebrate TPC3 NAADP-sensitivity exist [45,46]. Figure 2 summarizes the known or suggested activation/regulation mechanisms of TPCs [10,12,[47][48][49][50][51].…”
Section: Activation Mechanismsmentioning
confidence: 99%
“…In most eukaryotic cells, but not in plants or yeast, nicotinic acid adenine dinucleotide phosphate (NAADP) triggers the release of Ca 2+ ions from acidic intracellular stores, causing temporary increases in the cytosolic Ca 2+ ion concentration [11,30], influencing biological processes ranging from cell differentiation to cardiac function [31][32][33]. Fluorescence Ca 2+ -imaging experiments suggest that NAADP triggers Ca 2+ release and cytoplasmic activation (Ca a from acidic Ca 2+ stores containing TPC1-3 [11,[34][35][36]. However, photoaffinity labeling experiments with 32 Plabeled NAADP show that it does not directly bind TPCs [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…In most eukaryotic cells, but not in plants or yeast, nicotinic acid adenine dinucleotide phosphate (NAADP) triggers the release of Ca 2+ -ions from acidic intracellular stores, causing temporary increases in the cytosolic Ca 2+ -ion concentration[11,30], influencing biological processes ranging from cell differentiation to cardiac function[3133]. Fluorescence Ca 2+ -imaging experiments suggest that NAADP triggers Ca 2+ -release from acidic Ca 2+ -stores containing TPC1-3[11,3436]. However, photoaffinity labeling experiments with 32 P-labeled NAADP show that it does not directly bind TPCs[37,38].…”
Section: Main Textmentioning
confidence: 99%